Dietary Saturated Fat Promotes Development of Hepatic Inflammation Through Toll‐Like Receptor 4 in Mice. Issue 7 (8th December 2015) - Sutter, Alton G.; Palanisamy, Arun P.; Lench, Julie H.; Esckilsen, Scott; Geng, Tuoyu; Lewin, David N.B.; Cowart, Lauren A.; Chavin, Kenneth D.
ABSTRACT: Nonalcoholic steatohepatitis (NASH) is currently the third most common cause of end stage liver disease necessitating transplantation. The question remains how inflammation and NASH develop in the setting of nonalcoholic fatty liver disease (NAFLD) and steatosis. Understand the roles of toll‐like receptor 4 (TLR4) and dietary fats in the development of hepatic inflammation. Wild‐type and TLR4 KO mice were fed a standard high fat diet (LD), a high saturated fat diet (MD), or an isocaloric control diet (CD). Sera and tissue were analyzed for development of hepatic steatosis, inflammation, and injury. MD induced features of hepatic steatosis and inflammation in wild‐type, but not in TLR4 KO, mice. TLR4 KO prevented MD induced increases in NAFLD activity scores, serum alanine aminotransferase levels, and inflammatory cytokine expression. Inflammatory cell infiltration and cytokine expression were also lower in the TLR4 KO mice livers than wild‐type mice fed MD. Hepatic expression of Collagen I transcripts and collagen deposition were also decreased in the TLR4 KO MD animals. Results show that TLR4 plays a critical role in the effects of dietary fat composition on the development of hepatic steatosis, inflammation, and injury consistent with nonalcoholic steatohepatitis. J. Cell. Biochem. 117: 1613–1621, 2016. © 2015 Wiley Periodicals, Inc.